Influence of subclinical hypothyroidism and brain-derived neurotropic factor on telomere length dynamics in type 1 diabetic pregnancies and their newborns - Josip Djelmis; Marina Ivanisevic (Scientific Reports)
Abstract Thyroid dysfunctions are common in type 1 diabetes mellitus (T1DM) pregnancies, impacting embryogenesis and fetal neurodevelopment. This study investigates the effects of subclinical hypothyroidism and BDNF (Brain-derived neurotrophic factor) telomere length in T1DM mothers and their newborns. In a recent study, researchers found an inverse relationship between TSH (thyroid-stimulating hormone) levels and telomere length in the cord blood of newborns. This was prospective cohort analysis of 70 mothers and their newborns with T1DM. The study measured leukocyte telomere length (LTL) in maternal and neonatal samples. Subclinical hypothyroidism during the first trimester was characterized by TSH levels ranging from 2.5 to 5.0 mIU/L alongside normal free thyroxine (FT4) concentrations. In this study, we proved that maternal telomere length predicts telomere length in the newborn. Furthermore, we investigated the influence of maternal hypothyroidism on telomere length in the newborn. Maternal hypothyroidism in the first trimester of pregnancy has a strong influence on the shortening of newborn telomeres. BDNF has a positive effect on maternal and newborn telomere length. These results can have an important impact on the subsequent development of a child born to a diabetic mother. Health and disease associated with telomere length later in life may be programmed at birth.